PENINGKATAN KAPASITAS APARATUR DESA MELALUI PELATIHAN MANAJEMEN KELEMBAGAAN DESA BAGI SEKRETARIS DESA - Mulyana, Nana; Meiliyana, Meiliyana; Hermawan, Dedy (Prosiding Pengabdian FISIP Unila, 2012)
Implementation Activities Community Services is located in the District Jatiagung South Lampung. The method used in the form of lectures and discussion / FAQ. Thus, the evaluation design used was a quantitative evaluation through pre-test and post-test and evaluation qualitatively through discussion / question and answer with monitoring during the extension / dissemination of the material presented during the process of counseling / socialization takes place between the participants in the material renderer. Of implementation, it can be produced the conclusion that the management had understood the concept of village institutions and policies outline the rules governing the content of the GOI, has understood mechanisms and normative regulations in the management of village institutions and have understood the position of rural community participation in management activities of institutional by members of the village by village in the district secretaries forum Jatiagung South Lampung regency. Keywords: Aparateur Capacity, Villages Institution